Association Between the Neutrophil-To-Lymphocyte Ratio and Diabetes Secondary to Exocrine Pancreatic Disorders - Chen, Guanhua; Tan, Chunlu; Liu, Xubao; Chen, Yonghua (Frontiers in Endocrinology, 2022)
Background Diabetes mellitus among patients with exocrine pancreatic disorders is commonly known to be associated with chronic inflammation, including chronic pancreatitis and pancreatic ductal adenocarcinoma (PDAC). The neutrophil-to-lymphocyte ratio (NLR) is a novel marker that indicates the presence of various chronic inflammatory diseases, including type 2 diabetes (T2DM). However, no studies have examined the relationship between the NLR value and diabetes secondary to exocrine pancreatic disorders. Aim To determine whether the NLR value is associated with diabetes secondary to exocrine pancreatic disorders. Methods The medical data of subjects with confirmed pancreatic disease who were admitted to the Department of Pancreatic Surgery of our institution from August 2017 to October 2021 were obtained from the database and retrospectively analyzed. Anthropometric measures, laboratory data, including HbA1c, fasting insulin, and fasting C-peptide levels and the inflammatory index (white blood cell count, NLR, platelet-to-lymphocyte ration, monocyte-to-lymphocyte ratio) were recorded. The NLR is the ratio of neutrophils to lymphocytes. A homeostasis model (HOMA-B and HOMA-IR) was used to measure beta-cell dysfunction and insulin resistance. Results The NLR values of the diabetes secondary to exocrine pancreatic disorders group were significantly higher than those of the nondiabetic group (P=0.001). In multivariate logistic regression, after adjusting for covariates, high NLR values were found to be an independent risk factor for diabetes secondary to exocrine pancreatic disorders (OR: 1.37, 95% CI: 1.138-1.649, P=0.001). According to Spearman correlation analysis, the NLR was significantly correlated with fasting plasma glucose levels (P<0.0001) and HOMA2-IR values (P=0.02). Conclusion The NLR inflammation marker was significantly higher in subjects with diabetes secondary to exocrine pancreatic disorders and was associated with insulin resistance. NLR values may be reliable predictive markers for diabetes among patients with exocrine pancreatic disorders.